Claude Vivier ou la machine désirante - Richard, Robert (Éditions Varia, 2017)
"Claude Vivier, compositeur méconnu au Québec, est né à Montréal en 1948. Il meurt assassiné à Paris en 1983. Il a fait ses études avec Gilles Tremblay et Karlheinz Stockhausen. Son œuvre – qui contient une quarantaine de titres – est inclassable, s'inspirant de ou bougeant à travers des époques très différentes de l'histoire de la musique, depuis le Moyen Âge jusqu'à la musique dite « spectrale » des années 1980. C'est une œuvre d'une grande originalité, qui a choisi la fuite hors des attentes ou des formes prévues et qui a cherché à délirer les continents, les langues, les peuples."–From publisher's website

Claude Vivier at the End - Goldman, Jonathan (Contemporary Music and Spirituality, 2016)

Vivier reenacted: Singing beyond masculine - Novak, Jelena (New Sound: International Magazine for Music, 2015)
Vivier: A Night Report is a kind of poetical archive of musical details, protocols, experiences, concepts, memories, fears, desires and sorrows connected to Canadian composer Claude Vivier's (1948-1983) unusual destiny. All characters from Marko Nikodijević's opera originate from Vivier's life and works but they are re-indexed, or reenacted differently. The countertenor voice of Vivier is what primarily makes him different from all the rest of the characters. Even it could be claimed that the rest of the voices are dominated by Vivier's vocal presence on stage. Vivier stands as symbol for minority, queer, vulnerable. During his short life he was trying to get his own voice, voice as the personification of freedom and possibility to be heard. Finally he gets vivid, imaginative opera in which both his physical and personified voices are shining by creativity that his art emanate. He gets his singing voice, and he finally gets heard.

Claude Vivier: A Composer’s Life - Gilmore, Bob (University of Rochester Press, 2014)
Claude Vivier's haunting and expressive music has captivated audiences around the world. But the French-Canadian composer is remembered also because of the dramatic circumstances of his death: he was found murdered in his Paris apartment at the age of thirty-four. Given unrestricted access to Vivier's archives and interviews with Vivier's family, teachers, friends, and colleagues, musicologist and biographer Bob Gilmore tells here the full story of Vivier's fascinating life, from his abandonment as a child in a Montreal orphanage to his posthumous acclaim as one of the leading composers of his generation. Expelled from a religious school at seventeen for "lack of maturity," Vivier gave up his ambition to join the priesthood to study composition. Between 1978 and 1981 Vivier wrote the works on which his reputation rests, including 'Lonely Child', 'Bouchara', and the operas 'Kopernikus' and 'Marco Polo'. He went to Paris in 1982 to work on a new opera, the composition of which was interrupted by his murder. On his desk was the manuscript of his last work, uncannily entitled "Do You Believe in the Immortality of the Soul?" Vivier's is a tragic but life-affirming story, intimately connected to his passionate music. Bob Gilmore is a musicologist and performer and teaches at Brunel University in London. He is the author of 'Harry Partch: A Biography'.